Challenges and Opportunities in Using Electronic Prototyping as a Maker Tool - Lima, Adelmo; Trevisan, Daniela Gorski (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
The popularization of electronic prototyping kits, such as Arduino and BBC micro:bit, has allowed people from different areas to be able to create interactive devices using electronic components, quickly and at a low financial cost. As a large part of this audience does not have specialized knowledge, electronics and programming are the biggest challenges during the learning and creation process. This work aims to identify approaches that facilitate overcoming the obstacles faced when using electronic prototyping as a maker tool. A Rapid Review was carried out through database research and the snowballing technique. From the review, 54 articles were selected and analyzed according to the advantages and limitations of the approaches, the target audience, how it was tested with users, level of reproducibility and challenges for using the approaches in Brazil. Additionally, we have conducted three workshops with six graduated students interested in using this approach as maker tool, in order to identify challenges and difficulties during the learning and creation process. Our findings culminated in a set of approaches which could be considered to overcome part of the problems identified as well as which gaps still need to be covered with new solutions.